(untitled) (Transport systems and technologies, 2022)
This paper explores the practice of using ash and slag and fly ash from thermal power plants in road construction as one of the ways to dispose of industrial waste. The purpose of the study is to determine the chemica l composition of TPP ash and slag to study the possibility of using it as a raw material for road construction. To achieve the goal, the following tasks were set: to determine the main physical and chemical properties of ash and ash and slag from thermal power plants, to give an environmental assessment of the use of these wastes in road construction. Chemical analysis of ash and slag from Zmievskaya, Krivorozhskaya, Trypilskaya, Slavyanskaya TPPs was carried out to determine the main components: SiO2, Al2O3, Fe2O3, CaO, MgO, SO3, Nа2О and К2О. The content of heavy metals was determined using the method of atomic absorption analysis. The migration ability of heavy metal compounds from the roadway using ash and slag in the construction of roads has been studied using the construction of concentration-logarithmic diagrams. To predict the migration of heavy metal compounds into the environment when they are used in road construction, a separate dependence of the concentration of the most probable ions was plotted (for example, cuprum) [Cu(OH)n 2-n] on the pH of the environment. The lack of migration of cuprum compounds in a neutral and alkaline environment has been proven, which makes their use safe. Similar calculations were made for other metals.